Cost-effectiveness of the i-gel supraglottic airway device compared to tracheal intubation during out-of-hospital cardiac arrest: Findings from the AIRWAYS-2 randomised controlled trial. (October 2021) - Stokes, Elizabeth A.; Lazaroo, Michelle J.; Clout, Madeleine; Brett, Stephen J.; Black, Sarah; Kirby, Kim; Nolan, Jerry P.; Reeves, Barnaby C.; Robinson, Maria; Rogers, Chris A.; Scott, Lauren J.; Smartt, Helena; et al.
Abstract: Aim: Optimal airway management during out-of-hospital cardiac arrest (OHCA) is uncertain. Complications from tracheal intubation (TI) may be avoided with supraglottic airway (SGA) devices. The AIRWAYS-2 cluster randomised controlled trial (ISRCTN08256118) compared the i-gel SGA with TI as the initial advanced airway management (AAM) strategy by paramedics treating adults with non-traumatic OHCA. This paper reports the trial cost-effectiveness analysis. Methods: A within-trial cost-effectiveness analysis of the i-gel compared with TI was conducted, with a six-month time horizon, from the perspective of the UK National Health Service (NHS) and personal social services. The primary outcome measure was quality-adjusted life years (QALYs), estimated using the EQ-5D-5L questionnaire. Multilevel linear regression modelling was used to account for clustering by paramedic when combining costs and outcomes. Results: 9296 eligible patients were attended by 1382 trial paramedics and enrolled in the AIRWAYS-2 trial (4410 TI, 4886 i-gel). Mean QALYs to six months were 0.03 in both groups (i-gel minus TI difference −0.0015, 95% CI –0.0059 to 0.0028). Total costs per participant up to six months post-OHCA were £3570 and £3413 in the i-gel and TI groups respectively (mean difference £157, 95% CI –£270 to £583). Based on mean difference point estimates, TI was more effective and less costly than i-gel; however differences were small and there was great uncertainty around these results. Conclusion: The small differences between groups in QALYs and costs shows no difference in the cost-effectiveness of the i-gel and TI when used as the initial AAM strategy in adults with non-traumatic OHCA.